2011
DOI: 10.1021/jp1092509
|View full text |Cite
|
Sign up to set email alerts
|

Cluster-Models for Uranyl(VI) Adsorption on α-Alumina

Abstract: Aqueous complexation, adsorption, and redox chemistry of actinide species at mineral surfaces have a significant impact on their transport and reactive behavior in chemically and physically heterogeneous environments. The adsorption configurations and energies of microsolvated uranyl dication species, UO(2)(H(2)O)(n)(2+), were determined on fully hydroxylated and proton-deficient α-alumina(0001)-like finite cluster models. The significant size of the models provides faithful representations of features that ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 57 publications
3
37
0
1
Order By: Relevance
“…[11][12][13][14][15][16] In addition, computational methods are becoming popular in this field. 17 Density functional calculations have been carried out to study uranyl adsorption on the surfaces of a-alumina, 18,19 kaolinite, 20,21 and gibbsite. 22 Thus far, only force-field based molecular dynamics simulations were used to explore uranyl adsorption on basal surfaces of 2 : 1 clays, i.e.…”
Section: +mentioning
confidence: 99%
“…[11][12][13][14][15][16] In addition, computational methods are becoming popular in this field. 17 Density functional calculations have been carried out to study uranyl adsorption on the surfaces of a-alumina, 18,19 kaolinite, 20,21 and gibbsite. 22 Thus far, only force-field based molecular dynamics simulations were used to explore uranyl adsorption on basal surfaces of 2 : 1 clays, i.e.…”
Section: +mentioning
confidence: 99%
“…The DFT calculation results showed that the binding energy ( E bd ) of [HOOC‐GOs···UO 2 ] 2+ (12.1 kcal/mol) was greater than that of [GOs‐O···UO 2 ] 2+ (10.2 kcal/mol), suggesting that UO22+ favored binding with the –COOH group over the –O– group. The low E bd value of [G···UO 2 ] 2+ (8.1 kcal/mol) indicated that the sorption of U(VI) on rGOs was physical adsorption (8 kcal/mol) . The higher E bd values of [GOs···U(OH)O 2 ] 2+ (45.5 kcal/mol) and [GOs‐OH···U(OH)O 2 ] 2+ (42.8 kcal/mol) were attributed to OH abstraction from GOs, resulting in the chemical sorption of U(VI) on GOs and HOOC‐GOs (Figure ).…”
Section: Efficient Removal Of Heavy‐metal Ions From Aqueous Solutionsmentioning
confidence: 99%
“…To mimic the surface, we employed the embedded cluster method, an accepted and used widely method in metal oxide catalysts surfaces simulating, [44,45] and constructed two embedded cluster models with experimental lattice constant as seen in Figure 2. The embedded cluster models consisted of 18 atomic layers, and every layer was in the symmetry of C 3v (around Zaxis).…”
Section: Surface Models and Computational Detailsmentioning
confidence: 99%